2020
DOI: 10.1186/s12884-020-03088-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with unplanned pregnancy among women in Koshu, Japan: cross-sectional evidence from Project Koshu, 2011–2016

Abstract: Background: Unplanned pregnancy is a public health issue with adverse consequences for maternal and neonatal health. In Japan, the prevalence of unplanned pregnancy was 46.2% in 2002. However, few studies have investigated this topic, and there is little recent data from Japan. We described and examined the prevalence and determinants of unplanned pregnancy among rural women in Japan from 2011 to 2016. Methods: We used cross-sectional data from a community-based cohort study (Project Koshu). Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
(86 reference statements)
1
7
0
Order By: Relevance
“…Multivariable analysis has shown that women’s desire to avoid pregnancy is associated with age, relationship status and number of children, which is consistent with the wider literature on the determinants of pregnancy intention 8 27–32. Future analyses could consider how desire to avoid pregnancy changes over time and as external factors, such as relationship status and education level, change.…”
Section: Discussionsupporting
confidence: 76%
“…Multivariable analysis has shown that women’s desire to avoid pregnancy is associated with age, relationship status and number of children, which is consistent with the wider literature on the determinants of pregnancy intention 8 27–32. Future analyses could consider how desire to avoid pregnancy changes over time and as external factors, such as relationship status and education level, change.…”
Section: Discussionsupporting
confidence: 76%
“…Our finding that late- or non-stoppers initiate prenatal care later and have fewer face-to-face visits with the midwife could possibly be explained by the pregnancy recognition time. Previous studies reported that smoking during pregnancy is associated with unplanned pregnancy [ 28 ], leading to a later initiation of care and less prenatal visits [ 29 ]. Although the late- or non-stoppers initiate maternal care significantly later, our results do not indicate that either early stoppers or late- or non- stoppers have inadequate use of care.…”
Section: Discussionmentioning
confidence: 99%
“…27 Of increasing importance in a world of rising non-communicable diseases is the reduced opportunity for pre-pregnancy optimization of chronic medical conditions such as diabetes and obesity as well as the impact on mental health conditions such as depression, or of the chance to review potentially teratogenic medications. 28…”
Section: Why Do We Need To Know About Pregnancy Intention?mentioning
confidence: 99%